Case Report: A giant right atrial appendage aneurysm in a child - Luo, Yulan; Yuan, Dou (Frontiers in Cardiovascular Medicine, 2024)
Right atrial appendage aneurysm is an extremely rare cardiac anomaly. With unclear etiology, there is still no standard treatment method. Clinical symptoms and complications are important indicators for surgical resection. A 2-year-old boy without obvious cardiac symptoms was diagnosed with a giant right atrial outpouching arising from the right atrial appendage by computed tomography. The right atrial outpouching measured approximately 95×43mm. Due to its large size and potential impact on function of right atrium and ventricle, the aneurysm was resected in surgery. During the surgery a 105×55mm noncontractile cystic structure was found locating on the right anterior side of the right atrium. No other abnormalities like intracavity thrombus were detected. The patient was discharged five days after surgery. Postoperative recovery was uneventful.